miRNAs: una nueva mirada de la enfermedad de Vogt-Koyanagi-Harada - Vega T., Fabián; Elizalde A., Nathaly; Valenzuela B., Rodrigo A.; Urzua S., Cristhian A.; Cuitiño T., Loreto (Revista Hospital Clínico Universidad de Chile, 2022)
Vogt-Koyanagi-Harada disease (VKH) is an autoimmune multisystemic syndrome that includes bilateral intraocular inflammation, associated with exudative retinal detachments, and systemic manifestations in the auditory, integumentary, and central nervous systems. The frequency of VKH disease in the world is variable, but in Santiago, Chile, it causes approximately 17% of non-infectious uveitis, an incidence 2 to 3-fold greater than in the USA or European countries. The evidence shows that the pathogenesis of VKH would be caused by cell-mediated autoimmunity directed against melanocytes present in the uveal tissue. CD4+ T lymphocytes (especially hyperactivity of Th17 and Th1 cells), B lymphocytes, cytokines (e.g., TGF-β, IL-2, IL-6, IL-23 and INF-γ) and chemokines appear to play an important role in the development of VKH. Several lines of evidence support that the pathogenesis of uveitis observed in VKH involves an altered pattern of micro-ribonucleic acids (miRNA) expression, driving the loss of immunological tolerance. In this review, we discuss the evidence related to regulation and altered expression of miRNA associated with Vogt-Koyanagi-Harada and other autoimmune diseases.